Once Again to the Question of Nomadic and Sedentiary Headquarters in Steppe Empires (on the example of Khazaria and Golden Horde) - Dmitry V. Vasiliev (Археология евразийских степей, 2025)
The article presents the results of a comparative study of the role of nomadic headquarters in the life of two nomadic states of Eastern Europe – the Golden Horde and the Khazar Khaganate. The name of the Golden Horde stationary capital - the city of Sarai – is a complete copy or translation into Persian of the Mongolian term “horde”, more understandable to the nomadic aristocracy of the Ulus of Jochi. It is the nomadic headquarters, and not the sedentary capital, that is the place of concentration of power. Cities were just more or less stationary places in which (or near which) the headquarters stopped at certain times of the year in the process of further movement. It is assumed that all the cities with the word “Sarai” in their names were at some point the residence of the ruler. In the Northern Caspian region these are Sarai, Sarai al-Jadid, Saraichik, Ak-Sarai as well as Gulistan lis-Saray. According to the location of these cities it is possible to lay out the migration route of the Khan's headquarters. In the Khazar period there is a similar picture, only urban life is at an incomparably lower level. The ruler of the state moves along the established route from the Lower Volga to Perevoloka, then along the Don to the Sea of Azov, then to Taman, and from there along the Kuban and Manych - back to the Lower Volga. This almost year-round movement can be called “polyudye” – the main way of exercising power in the early feudal state. It is suggested that Khazar “castles” - small fortresses with an undeveloped cultural layer – are a kind of analogue of “pogosts” (“guest yards”) – places for collecting tribute and temporary camps for the royal squad.